Hubungan Motivasi Belajar dengan Kedisiplinan Belajar Siswa di SMK Islam Nurul Qolbi Setanggor Lombok Tengah - zulkarnaen, zulkarnaen (Al-INSAN Jurnal Bimbingan Konseling dan Dakwah Islam, 2024)
The background to this research is based on the results of observations at Nurul Qolbi Stanggor Islamic Vocational School, namely that there is still a lack of student motivation to learn and student learning discipline. This can be seen from the lack of student compliance in implementing school regulations such as; not going to school without permission, coming to school late, some students sometimes skipping classes, disobeying teacher orders, not doing assignments, and so on, problems like these will affect PBM and student achievement levels. The problem formulation in this research is whether there is a relationship between student learning motivation and the learning discipline of Nurul Qolbi Stanggor Islamic Vocational School students. The aim of this research is to determine the relationship between student learning motivation and learning discipline of Nurul Qolbi Stanggor Islamic Vocational School students. The research method used by this researcher is a quantitative approach because it pays attention to the goals to be achieved and the problems to be solved so that it can provide research results that have reliability and validity. The population in this study was all 30 scout students. The data collection methods used are the scale method, observation method and documentation method. This research analysis uses Product Moment Correlation analysis, calculations assisted using the SPSS version 22.0 for Windows program. Based on the results of this research, it shows that there is a positive and significant relationship between students' learning motivation and their learning discipline. It is known that the majority of research student learning motivation variables are in the medium category, namely (63%) of 30 respondents and are located in the interval 102-160, and the majority of learning discipline variables are in the medium category, namely (83%) of 30 respondents are located in the interval 99-127. From the analysis of hypothesis testing through the product moment correlation formula from Pearson, namely rxy of 0.732 at a significance level of p of 0.000 (p < 0.05) or it can be proven by comparing the calculated r value with r_ table, the value obtained is (r_hit= 0.732 and r_ table= 0.361 at a significance level of 0.05 with a size of N=30) because (r_hit > r_table) the results are significant and the proposed hypothesis is accepted. This means that Ha is accepted and Ho is rejected. With an effective contribution from student learning motivation and student learning discipline amounting to (53.5%), while the rest is influenced by other factors.